2017
DOI: 10.1002/cne.24214
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and neurochemical differences in peptidergic nerve fibers of the mouse vagina

Abstract: The vagina is innervated by a complex arrangement of sensory, sympathetic, and parasympathetic nerve fibers that contain classical transmitters plus an array of neuropeptides and enzymes known to regulate diverse processes including blood flow and nociception. The neurochemical characteristics and distributions of peptide-containing nerves in the mouse vagina are unknown. This study used multiple labeling immunohistochemistry, confocal maging and analysis to investigate the presence and colocalization of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…Previous studies found most neurons of the inferior mesenteric ganglia are immunoreactive for NPY and TH but none are immunorecative for VIP, whereas many neurons of the major pelvic ganglia are immunoreactive for both NPY and VIP. 8,21 In addition to identifying innervation differences in distinct layers of the urethral wall, the present study noted differences in proximal and distal segments of the urethra.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…Previous studies found most neurons of the inferior mesenteric ganglia are immunoreactive for NPY and TH but none are immunorecative for VIP, whereas many neurons of the major pelvic ganglia are immunoreactive for both NPY and VIP. 8,21 In addition to identifying innervation differences in distinct layers of the urethral wall, the present study noted differences in proximal and distal segments of the urethra.…”
Section: Discussionmentioning
confidence: 53%
“…Functional studies show VIP relaxes urethral smooth muscle . CGRP+VIP+fibers are common in the mouse vagina but we identified no fibers showing this specific combination of immunoreactivities in the urethra.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations